2012
DOI: 10.1007/s00296-012-2641-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening for latent TB in patients with rheumatic disorders prior to biologic agents in a ‘high-risk’ TB population: comparison of two interferon gamma release assays

Abstract: Patients with rheumatic disorders treated with TNF inhibitors are at increased risk of developing TB. There is no 'gold-standard' for the diagnosis of latent TB prior to initiation of biologic agents. We report our own experience of comparing two interferon gamma release assays (IGRAs) in screening for latent TB in a 'high-risk' TB area in patients with rheumatic disorders. The study demonstrated good concordance between the two tests. We believe the additional cost of these assays is justified in high-risk po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Given the low agreement between TST and IGRA,42 44 52–71 performing both tests can also be considered in cases of high suspicion for latent TB and/or in high-endemic countries 58 70 72. Concordance between different IGRAs (Quantiferon and EliSPOT) is good thus one is not recommended over the other 47 73–75. In addition, although there is no robust evidence for the usefulness of chest X-Ray, the TF considered it appropriate that this should be included in the TB- screening procedures, especially as a negative IGRA or TST cannot exclude active TB or rule out latent TB 76.…”
Section: Resultsmentioning
confidence: 99%
“…Given the low agreement between TST and IGRA,42 44 52–71 performing both tests can also be considered in cases of high suspicion for latent TB and/or in high-endemic countries 58 70 72. Concordance between different IGRAs (Quantiferon and EliSPOT) is good thus one is not recommended over the other 47 73–75. In addition, although there is no robust evidence for the usefulness of chest X-Ray, the TF considered it appropriate that this should be included in the TB- screening procedures, especially as a negative IGRA or TST cannot exclude active TB or rule out latent TB 76.…”
Section: Resultsmentioning
confidence: 99%
“…It has been a challenge to determine the usefulness of IGRAs for LTBI monitoring during TNF-α antagonist therapy. Several studies [ 8 , 19 , 20 , 36 , 37 ] have evaluated IGRAs for LTBI screening in these patients, suggesting that QFT-GIT, T-SPOT.TB, and TST are all acceptable, but imperfect tests for definitive LTBI diagnosis. Based on the results of our study, we suggest that T-SPOT.TB test should be included in the initial evaluation as well as in follow-up protocols for patients with rheumatic diseases receiving TNF-α antagonist therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Disagreement between TST and IGRA has led some authors to suggest that both tests should be performed in high-risk patients (travelling or coming from endemic regions) and/or in countries with high TB-burden 39 49 51. On the other hand, Quantiferon and enzyme-linked immunosorbent spot (ELISpot), two IGRA test platforms, appear to have good concordance52–55 (table 2). Several studies have shown that IGRA display a better performance compared with TST, having better sensitivity and specificity and being associated more closely with TB risk factors 13 14 17 19 25 30 55–57.…”
Section: Resultsmentioning
confidence: 99%